Handbook of psychopharmacology. Principles of behavioral pharmacology - Iversion, Leslie L. (Plenum Press, 1977)
Contens of this book include: Bichemical principles and techniques in neuropharmacology; Principles of receptor research; Synaptic modulator research; Biogenic amine receptors; Principles of bihavioal pharmacology.